Environmental Design Criteria For a TLP In Cyclonic Conditions. - Higgins, Stuart; Hinwood, Jon (1999)
For the first phase of this research a six degree of freedom frequency domain model of a Tension Leg Platform (TLP), which includes the effects of non-collinear wind, wave and current, has been developed to determine the extreme response and sensitivities of environmental input. The model includes the steady forcing effects due to current and wave interaction, wind and wave drift. The dynamic "effects include Morison type forces due to inertia and drag, spatially correlated wind and slowly varying wave drift. The response model is used to evaluate four limit states of a TLP, namely minimum and maximum tension, maximum offset and minimum airgap. The second phase of this research has developed a method to evaluate the return period of required response and then select the mostly likely combination of environmental parameters to aid in design screening. The technique combines the response model and Inverse First Order Reliability Method (FORM) through a non-linear optimization routine.